Two-photon ESIPT-based fluorescent probe using 4-hydroxyisoindoline-1,3-dione for the detection of peroxynitrite - Wu, Luling; Tian, Xue; Lee, Dong Joon; Yoon, Juyoung; Lim, Chang Su; Kim, Hwan Myung; James, Tony D. (Chemical Communications, 2021)
Excited-state intramolecular proton transfer (ESIPT)-based fluorophores with two-photon excitation fluorescence (TPEF) are rare. Our aim with this research was to develop ESIPT-based fluorophores exhibiting TPEF. Herein, we used 4-hydroxyisoindoline-1,3-dione as a scaffold to develop a two-photon fluorescent probe BHID-Bpin, for the detection of peroxynitrite (ONOO-). BHID-Bpin exhibits excellent selectivity, sensitivity, and fast response towards ONOO- in PBS buffer solution (10 mM, pH = 7.40). Additionally, BHID-Bpin displays high photo-stability under two-photon irradiation at 750 nm. Furthermore, the probe can image endogenous ONOO- in HeLa cells and exogenous ONOO- in rat hippocampal slices at a depth of 110 μm.
Keywords: Excited-state intramolecular proton transfer; Fast response; Fluorescent probes; PBS buffer solutions; Peroxynitrites; Photo-stability; Photon irradiation; Two photon; Two photon excitation fluorescence; Two-photon excited